Hand Gesture Recognition From Wrist-Worn Camera for Human–Machine Interaction - Hong-Quan Nguyen; Trung-Hieu Le; Trung-Kien Tran; Hoang-Nhat Tran; Thanh-Hai Tran; Thi-Lan Le; Hai Vu; Cuong Pham; Thanh Phuong Nguyen; Huu Thanh Nguyen (IEEE Access)
In this work, we study the ability to use hand gestures for human-machine interaction from wrist-worn sensors. Towards this goal, we design a wrist-worn prototype to capture RGB video stream of hand gestures. Then we built a new wrist-worn gesture dataset (named WiGes) with various subjects in interaction with home appliances in different environments. To the best of our knowledge, this is the first benchmark released for studying hand gestures from a wrist-worn camera. We then evaluate various CNN models for vision-based recognition. Furthermore, we deeply analyze the models that produce the best trade-off between accuracy, memory requirement, and computational cost. We point out that among studied architectures, MoviNet produces the highest accuracy. Then, we introduce a new MoviNet-based two-stream architecture that takes both RGB and optical flow into account. Our proposed architecture increases the Top-1 accuracy by 1.36% and 3.67% according to two evaluation protocols. Our dataset, baselines, and proposed model analysis give instructive recommendations for human-machine interaction using hand-held devices.